Auto Result Analyser and Sender - M.Afrin Zulaiha, A; K.A. Mohamed Junaid, Dr (International Journal of Engineering and Technology, 2018)
Web development has taken various steps to strengthen knowledge base activities and supporting the client ideas. A pertinent portal is generated to maintainand store records which can be used by many educational institutions. The enhancement is made by using auto notification of electronic mail by specifying the email address for each student. Auto Result Analyser and Sender (ARAS) proves out to be more task effective and predominantly reliable. The information regarding student enrolment, internships are provided.The real-time reporting can be done once results are published and sent as mail/SMS to the registered students/parents. The performance wise comparison among various colleges and the students can be carried out with the usage of statistical analysis. SQL supports all the queries related to the database and the table insertions.Â Â Â